Flipped classroom in physical education: a systematic review of implementation and student outcomes - Aidil Syaputra; Jeki Haryanto; Eval Edmizal (Indonesian Institute For Counseling, Education and Therapy, 2025)
The flipped classroom has emerged as a prominent pedagogical innovation, yet its application within physical education-a domain defined by embodied, psychomotor learning-remains comparatively underexamined and empirically fragmented. This systematic literature review synthesises evidence on how the flipped classroom has been implemented in physical education and what effects it produces on student outcomes. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) framework, drawing records from the Scopus database through a structured Boolean search of title, abstract, and keyword fields. The initial search returned 161 records; after removing 14 duplicates, screening 147 titles and abstracts, and assessing 60 full texts against predefined eligibility criteria, 23 studies were included. Study quality was appraised with the FICO framework (Focus, Information, Context, Outcome), retaining only studies that satisfied all four dimensions; because the included studies were highly heterogeneous in design and outcome measurement, their findings were combined through thematic synthesis rather than meta-analytic pooling. Thematic synthesis identified five recurrent outcome domains: motor-skill learning, motivation, physical activity and engagement, cognitive knowledge, and student satisfaction. Across designs, flipped approaches generally improved psychomotor performance, autonomous motivation, in-class activity time, and conceptual understanding, although effects on physical fitness were inconsistent. The review advances theoretical understanding of pre-class digital preparation in movement contexts and offers practical guidance for teachers, while underscoring the need for larger, longer, and methodologically rigorous trials across diverse educational settings.